Do Community Health Centers Have Contextual Effect on the Risk of Recurrence in Patient with Tuberculosis? A Multilevel Evidence from Surakarta, Central Java - Muvida, Muvida; Widyaningsih, Vitri; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Community Health Centers play